Polishing Resistance of Granite and Limestone Aggregate with Different Combination Ratio - Olivia, Tang Lih Lih (Universiti Malaysia Sarawak, (UNIMAS), 2020)
This research focused on the potential use of non-standard aggregates on surface wearing course of pavement so to improve the skid resistance of pavement. Skid resistance of road surfaces has crucial impact on road safety. Skid resistance is also known as surface friction. It is provided by the pavement surface to the tires to prevent cars from skidding along the pavement surface. Standard aggregates such as granite are commonly used in paving and make up about 75-80 per cent by asphalt concrete volume (AC) or 90-95 per cent by AC weight. Sarawak currently has several road build projects requiring extensive use of granite aggregates. Because of the limitation of granite aggregates, the importation of these materials has increased the cost of transportation hence the overall cost of construction. There is no standard specification for combination of standard aggregates and substandard aggregates in Malaysia. Therefore, the objective of the study is to investigate the polishing resistance and suitability of combination of limestone aggregate with granite aggregate as surface course. Granite aggregate served as standard aggregate while limestone aggregate served as non-standard aggregate. A total of 4 sets of granite aggregate and limestone aggregate samples, 2 sets of granite aggregates and 2 sets of limestone aggregate samples was prepared. Laboratory tests involved Polishing of Aggregates using accelerated polishing machine and Skid Resistance Test using portable pendulum skid resistance tester; according to the standards outlined in British Standard 812: Part 114: 1989. Based on the results, the engineering performance of limestone aggregate complied with all the specified requirements in JKR standard specification and only suitable for roads with low volume roads.